(untitled) (Research, Society and Development, 2021)
The mineral sector have great importance in the Brazilian economy, however it can be seen as a villain in the environmental area, mainly due to the negative impacts caused by the disposal of tailings from mineral activities. In order to assist in the planning of risk management actions, this study tested a simplified model adapted to generate hypothetical leakage scenarios from an alumina tailings deposit, located in the city of Barcarena-PA. The simulations were carried out based on the LNEC method with adaptations for analyzing the tailings deposit. For this, tests were carried out to define the discharge intervals capable of generating spots with different degrees of risk to flooding (high, medium and low) throughout the Murucupi River. The results indicated the risk of flooding in Vila dos Cabanos, Itupanema and Laranjal. It is concluded that the LNEC method with adjustments can be used in the generation of the flooding spot of tailings deposits to identify risk areas and indicate priority areas for public sector actions, being, therefore, an important risk management tool.